Comparative Study of Intralesional Triamcinolone Alone and Combination with 5-Flurourouracil in Management of Keloid (The Planet, 2023)
Background: Keloids is an excessive proliferation of dermal fibroblasts, spontaneously or following any types of skin injury. Both intralesional triamcinolone alone and its combination with 5-flurourouracil are used in the management of keloid. The aim of this study was to compare the efficacy and outcomes oftriamcinolone alone and its combination with 5-flurourouracil in the management of keloid. Methods and materials: This comparative study was conducted at the department of Dermatology and Venereology in Cumilla Medical College Hospital, Cumilla, Bangladesh during the period from June 2018 to May 2019. Results: In this study,the mean (±SD) VancouverScar Scale scores regarding the height, vascularity, pliability and pigmentation at baseline were recorded before starting the treatment tenures. At the final follow-up period, regarding the height, and pigmentation among B (TAC+5-FU) group patients, the mean (±SD) vancouver scar scale scores were found significantly lower than those among A (TAC) group patients and the P values were 0.022 and 0.012 respectively. Besides these, during the final follow-up period, in group A, the mean pain and pruritus scores were found 0.19 and 0.44 respectively which were found less enough than 0.08 and 0.29 in group B respectively. Conclusion: This current comparative study has shown that the combination therapy of triamcinolone acetonide and 5-flourouracil (TAC+5-FU) is more effective and faster in response with fewer side effects compared to that ofintralesional triamcinolone acetonide alone(TAC) alone in the treatment of keloids.
Keywords: Keloid; 5-fluorouracil; Vancouver scar scale; Triamcinolone acetonide